Analisis Gaya Belajar Kinestetik Taruna Politeknik Pelayaran Barombong - Nursyam; Jeihn Novita C. Budiman; Rusdi (Politeknik Pelayaran Barombong, 2020)
This study aims to describe the kinesthetic learning styles of cadets of the Barombong Shipping Polytechnic class 64. This study is a qualitative study to describe the kinesthetic learning styles of cadets of class 64. The research respondents were all cadets of class 64 who met the research criteria, totaling 153 cadets. The research instrument uses the VARK version 8.0 test which has been translated into Indonesian and analyzed using the percentage form that describes the frequency characteristics of cadet learning styles. The tendency of the cadets' learning style studied in this study is the Kinetics learning style. Through this study, it was found that the kinesthetic learning style of the 64th generation of cadets was the most dominant with a percentage of 51.6% of all research respondents.